Reversible and Quantum Circuits Optimization and Complexity Analysis - Abdessaied, Nabila; Drechsler, Rolf.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents a new optimization flow for quantum circuits realization. At the reversible level, optimization algorithms are presented to reduce the quantum cost. Then, new mapping approaches to decompose reversible circuits to quantum circuits using different quantum libraries are described. Finally, optimization techniques to reduce the quantum cost or the delay are applied to the resulting quantum circuits. Furthermore, this book studies the complexity of reversible circuits and quantum circuits from a theoretical perspective.
Chapter 1 Introduction -- Chapter 2 Background -- Chapter 3 Optimizations and Complexity Analysis on the Reversible Level -- Chapter 4 Optimization and Complexity Analysis on the Mapping Level -- Chapter 5 Optimizations and Complexity Analysis on the Quantum Level -- Chapter 6 Conclusions.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Electronics; Electronic Circuits and Systems; Processor Architectures; Electronics and Microelectronics, Instrumentation